China and Mozambique from comrades to capitalists - Alden, Chris 1959-; Chichava, Sérgio 1974- (Fanele, 2014)
"The wide range of reactions to greater Chinese involvement across Africa has varied from enthusiastic embrace by elites to caution from businesses, trade unions and civil society, and even hostility from some local communities. As a once-modest presence in Africa, China has rapidly grown to become one of Africa's top trading partners. Two-way trade surged from just over US$10 billion in 2000 to US$220 billion in 2012. China and Mozambique moves beyond the conventions of general surveys on China-Africa relations to explore real content and experiences of China's relationship with Mozambique." ... Back cover
Includes bibliographical references and index
Keywords: Investments, Chinese -- Mozambique; Wirtschaftsbeziehungen; China -- Foreign relations -- Mozambique; Mozambique -- Foreign economic relations -- China; Moçambique; China